The Other Space Race : Eisenhower and the Quest for Aerospace Security. - Sambaluk, Nicholas Michael (Transforming war., 2015)
The Other Space Race is a unique look at the early U.S. space program and how it both shaped and was shaped by politics during the Cold War. Eisenhower's New Look" expanded the role of the Air Force in national security, and ultimately allowed ambitious aerospace projects, namely the ;Dyna-Soar," a bomber equipped with nuclear weapons that would operate in space. Eisenhower's space policy was purely practical, creating a strong deterrent against the use of nuclear arms against the United States. With the Soviet launch of Sputnik in 1957, the political climate changed, and space travel became.